Association of CTLA4 and NOD2/CARD15 (N852S) Genes Single Nucleotide Polymorphisms with Inflammatory Bowel Disease in Iraqi Patients - Al-Rhman, Rand Manaf Abd; Alsaffar, Jinan Mohammed Jawad (Iraqi Journal of Science, 2025)
The present study was designed to examine single nucleotide polymorphisms (SNPs) of CTLA4 (rs231775) and NOD2/CARD15 (rs104895467) genes profiles that are related to etiology and pathogenesis of inflammatory bowel disease (IBD) in two groups of Iraqi patients (Crohn’s disease (CD) and ulcerative colitis (UC)). The frequency of the allele and genotypes were determined using polymerase chain reaction (PCR-RFLP) and then confirmed by sequence analysis. For CTLA4 (rs231775) SNP comparing IBD patients to controls revealed some significant variations. The GG genotype demonstrated a significant increased incidence in IBD patients than controls (62.4vs. 0.0%; OR = 238.69; pc = 5.7x10-9). In contrast, the AA genotype (14.1vs. 77.8%; OR = 0.05; pc= 8.5x10-9) appeared to have a decreased frequency in patients. Such as the A allele observed significantly decreased frequency in IBD patients compared to controls (25.9vs. 89.0%; OR = 0.04; pc = 6.6x10-9). While the G allele showed a significantly increased frequency in patients (74.1vs. 11.0%; OR = 22.91; pc=6.6x10-9). And for the NOD2/CARD15 (rs104895467) SNP indicated no significant association with the IBD. The genotype frequencies of the CTLA4 and NOD2/CARD15 SNPs also showed no significant variation between CD and UC patients.